Droplet formation in cold asymmetric nuclear matter in the quark-meson-coupling model - Krein, G. [UNESP]; Menezes, D. P.; Nielsen, M.; Providência, C. (Elsevier, 2000)
The quark-meson-coupling model is used to study droplet formation from the liquid-gas phase transition in cold asymmetric nuclear matter. The critical density and proton fraction for the phase transition are determined in the mean field approximation. Droplet properties are calculated in the Thomas-Fermi approximation. The electromagnetic field is explicitly included and its effects on droplet properties are studied. The results are compared with the ones obtained with the NL1 parametrization of the non-linear Walecka model. © 2000 Elsevier Science B.V.
Keywords: 12.39.-x; 21.65.+f; 24.10.Jv; 25.75.-q; Liquid-gas phase transition; Nuclear matter; Quark-meson-coupling model; Relativistic models